The reusability of baker's yeast (Saccharomyces cerevisiae) immobilized in calcium alginate and k-carrageenan/locust bean gum gel beads during repeated batch ethanolic fermentation - Tiuseco, Manolito Tamondong
The reusability of Saccharomyces cerevisiae when immobilize in 2% calcium alginate and 2.74% κappa-carrageenan/0.24% locust bean gum (LBG) during repeated batch ethanolic fermentation of rice washing was investigated using baker's yeast immobilized in gel beads 2 to 4 millimeters in diameter. Reusability was assessed based on the ability to reduce the soluble solids in the rice wash substrate and on release of yeast cells from the gel matrices into the rice washing substrate which can be related to the physical deterioration of the gel beads. Over a span of twenty fermentation days or batches, it was observed that calcium alginate-immobilized bakers's yeast was reusable for repeated-batch ethanolic fermentation. It had a greater capability to reduce soluble solids in substrate and had a lower range of yeast cell counts (colony-forming units per ml) than the κ-carrageenan/LBG-immobilized baker's yeast. The κ-carrageenan/LBG gel beads also need KCl supplementation of the rice wash substrate for reusability to reach the same numbers of batches. Overall, calcium alginate-immobilized baker's yeast may be considered to be more efficient in the bioconversion of substrate to ethanol and more physically stable than κ-carrageenan/LBG-immobilized baker's yeast when used in repeated-batch ethanolic fermentation of rice washing.